A resin composite material containing an eugenol derivative for intracanal post cementation and core build-up restoration. Issue 2 (February 2016) - Almaroof, A.; Rojo, L.; Mannocci, F.; Deb, S.
Abstract: Objectives: To formulate and evaluate new dual cured resin composite based on the inclusion of eugenyl methacrylate monomer (EgMA) with Bis-GMA/TEGDMA resin systems for intracanal post cementation and core build-up restoration of endodontically treated teeth. Methods: EgMA was synthesized and incorporated at 5% (BTEg5) or 10% (BTEg10) into dual-cure formulations. Curing properties, viscosity, T g, radiopacity, static and dynamic mechanical properties of the composites were determined and compared with Clearfil™DC Core-Plus, a commercial dual-cure, two-component composite. Statistical analysis of the data was performed with ANOVA and the Tukey's post-hoc test. Results: The experimental composites were successfully prepared, which exhibited excellent curing depths of 4.9, 4.7 and 4.2 mm for BTEg0, BTEg5 and BTEg10 respectively, which were significantly higher than Clearfil™DC. However, the inclusion of EgMA initially led to a lower degree of cure, which increased when measured at 24 h with values comparable to formulations without EgMA, indicating post-curing. The inclusion of EgMA also lowered the polymerization exotherm thereby reducing the potential of thermal damage to host tissue. Both thermal and viscoelastic analyses confirmed the ability of the monomer to reduce the stiffness of the composites by forming a branched network. The compressive strength of BTEg5 was significantly higher than the control whilst flexural strength increased significantly from 95.9 to 114.8 MPa (BTEg5) and 121.9 MPa (BTEg10). Radiopacity of the composites was equivalent to ∼3 mm Al allowing efficient diagnosis. Significance: The incorporation of EgMA within polymerizable formulations provides a novel approach to prepare reinforced resin composite material for intracanal post cementation and core build-up and the potential to impart antibacterial properties of eugenol to endodontic restorations.